Numerical Modelling of Subsea Cables and Pipelines - Reda, Ahmed (Curtin University, 2020)
The continuing rapid growth in the world’s energy demands, has resulted in oil and gas exploration and production moving towards offshore facilities and the expansion of renewable energy, in particular the use of offshore wind energy. The outcome of this research resolves issues in relation to subsea cables and pipelines including the compression limits, joints and crossings of subsea power cables, and the modelling of walking and anchoring for subsea pipelines.